A Ten‐year Program Evaluation of an Emergency Medicine Scholarly Track in Education Using a Qualitative Approach. Issue 3 (22nd May 2017) - Schnapp, Benjamin H.; Fant, Abra L.; Gisondi, Michael A.
Abstract: Background: Residency scholarly tracks have allowed training programs to better prepare residents for a future in academia. Despite their success, however, few evaluations of these scholarly tracks have been completed to ensure they are meeting the goals of their stakeholders. Objective: The objective was to evaluate the education scholarly track at Northwestern University Emergency Medicine by querying key stakeholders on the current state of the track and its ideal state. Methods: Current emergency medicine residents, faculty, and track alumni were identified as essential stakeholders. Their perspectives on the track were elicited with a focus group and online survey, respectively, and responses were analyzed using grounded theory. Results: Four distinct themes emerged from the analysis as critical to the track: "education skills and learning theory, " "education research methodology, " "leadership, " and "collaboration." Conclusion: These themes will be used to inform further development of the track. A similar self‐reflection process may benefit other programs with scholarly tracks.